Spectrum of Chromosomal Abnormalities Detected by Chromosomal Microarray in Fetuses with Abnormal Ultrasound Findings: A Prospective Observational Cohort Study - Redishetty, Saritha; Pula, Ravikanth; Mallidi, Priyanka; Nerakh, Gayatri (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVES: Fetal structural anomalies (FSAs) occur in approximately 3% of pregnancies, increasing perinatal morbidity and mortality. While conventional karyotyping has been a cornerstone of prenatal testing, its limitations in detecting sub-microscopic chromosomal abnormalities necessitate Chromosomal Microarray Analysis (CMA). CMA offers superior resolution, detecting copy number variants (CNVs) undetected by karyotyping. The objectives of the study are to evaluate the diagnostic utility of CMA in fetuses with abnormal ultrasound findings and to determine its additional yield over karyotyping. STUDY DESIGN: A prospective observational cohort study was conducted at a tertiary care center in South India over 18 months, including 226 singleton pregnancies with fetal structural abnormalities or soft markers. Samples collected via amniocentesis or chorionic villous sampling were analyzed using an Agilent 8x60K array. Results were interpreted based on the GRCh37/hg19 human reference genome, followed by pre- and post-test genetic counseling. Statistical analyses included descriptive and inferential methods. RESULTS: CMA detected chromosomal abnormalities in 50 cases (17.2%), providing an additional 5.1% diagnostic yield over karyotyping. Common aneuploidies included trisomy 21 (12 cases) and Turner syndrome (6 cases). Notable CNVs were identified in cases with increased nuchal translucency, unossified nasal bones, and central nervous system anomalies. The central nervous system was the most affected (32%), followed by musculoskeletal and cardiovascular systems. CONCLUSION: CMA enhances the detection of chromosomal abnormalities in fetuses with abnormal ultrasound findings, offering critical insights for prenatal diagnosis and parental decision-making. Genetic counseling remains integral to its application.